Drug Nanocrystals: Four Basic Prerequisites for Formulation Development and Scale-Up - Mohana Raghava Srivalli, Kale; Mishra, Brahmeshwar (Current Drug Targets, 2015)
Drug nanocrystals have been studied since the 1990s and there are already six therapeutic nanocrystal products on market and many more in clinical trials. Nanocrystals are encapsulating-carrier free nanoparticles wherein 100% drug loading could be achieved. This signifies that nanocrystals, among other nanoparticulate products, could be more easily manufactured even at the initial formulation development stages to evaluate the effect of size reduction on the bioavailability of drugs. Additionally, a drug nanocrystal is considered not as a generic product but as a “new drug” by FDA. Process characterization, equipment choice, robust formulation and stability are discussed as four basic prerequisites for formulation development and scale-up of drug nanocrystals. The fast growing and relatively superior market profile of nanocrystals amongst other nanoparticle systems is due to their rational formulation design and production simplicity. In this emerging scenario, keeping an eye on the four basic prerequisites can further improve the success of drug nanocrystals.
Keywords: formulation